Learning Strategies In Improving The Independence Of Blind Children - Salwa, Cut Amelia; Uzma, Fauzatul; Br.Art, Feni Happynis; Hijriati (UNIB Press, 2025)
Deaf children are an essential concern, especially at an early age, to provide independent learning that will be beneficial in the future, as they are accustomed to being independent without the help of others. The purpose of the study was to identify and describe effective learning strategies in improving the independence of blind children in special schools (SLB), Bukesra Banda Aceh. This study uses a qualitative approach with a case study method, data collected through interviews with teachers and observation of teaching and learning activities. The results showed that the main strategies implemented include expository methods for the delivery of material in a structured manner, heuristic methods to foster independent and critical thinking, as well as a team teaching approach that allows more personalized guidance. In addition, schools use audio media such as audiobooks as alternative visual aids, ice-breaking activities to increase learning focus, and giving awards as a form of positive reinforcement to build motivation and social participation of children. The curriculum is tailored to each student's ability to create inclusive and adaptive learning. The findings of this study indicate that integrated and responsive learning strategies significantly support the development of academic and social independence of children with visual impairments, which can be seen from their increased initiative, confidence, and active participation in the learning process.